LAJU PERTUMBUHAN Pocillopora damicornis (Linnaeus, 1758), Acropora formosa (Dana, 1846) dan Acropora cervicornis (Lammarck, 1816) YANG DI TRANSPLANTASI DI PERAIRAN TELUK TEMPURUNG KECAMATAN BATANG KAPAS KABUPATEN PESISIR SELATAN - Andani, Rolly - (STKIP PGRI Sumbar, 2014)
Coral reef ecosystem is a unique marine ecosystem and are in the tropics. This study was conducted to determine the growth rate of Pocillopora damicornis, Acropora formosa and Acropora cervicornis in transplantation in the waters of the Teluk Tempurung Kecamatan Batang Kapas Kabupaten Pesisir Selatan. The usefulness of this study is expected to provide scientific information about coral transplantation as an alternative method to preserve the coral reefs and as a reference for further researches. This study was conducted in November 2013 until March 2014. This research was conducted using an experimental method. In this study, the transplanted corals are three species, namely Pocillopora damicornis, Acropora formosa and Acropora cervicornis. Each coral fragment attached to the substrate, then the substrate is already affixed coral fragments on metal shelves arranged randomly. The results showed that the growth rate of the coral Pocillopora damicornis diameter after four months of its value ranges from + 0.28 mm to + 1.22 mm, diameter growth rate of Acropora formosa after four months of its value ranges from + 0.15 mm to + 0.41 mm and diameter growth rate of Acropora cervicornis after four months of its value ranges from + 0.12 mm to + 0.31 mm. The growth rate of the coral Pocillopora damicornis high after four months of its value ranges from + 1.90 mm to + 3.25 mm, the high growth rate of the coral Acropora formosa after four months of its value ranges from + 1.80 to + 3.00 mm and a high growth rate of coral Acropora cervicornis after four months of its value ranges from + 1.70 mm to + 2.55 mm. The survival rate of the coral Pocillopora damicornis 100 %, Acropora formosa 100 % and Acropora cervicornis 60%.